2002
DOI: 10.1080/15604280214939
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Endothelins: A Common Pathogenetic Mechanism in Chronic Diabetic Complications

Abstract: Endothelin (ET) peptides perform several physiological, vascular, and nonvascular functions and are widely distributed in a number of tissues. They are altered in several disease processes including diabetes. Alteration of ETs have been demonstrated in organs of chronic diabetic complications in both experimental and clinical studies. The majority of the effects of ET alteration in diabetes are due to altered vascular function. Furthermore, ET antagonists have been shown to prevent structural and functional ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 197 publications
(271 reference statements)
0
14
0
Order By: Relevance
“…[1][2][3][4][5]18 We have previously demonstrated an important role of hyperglycemia-induced ET-1 expression in increased ECM protein deposition. 4,15,18 We have also shown that hyperhexosemia-induced increased FN mRNA expression can be prevented by bosentan treatment in retinas and kidneys of both diabetic and galactose-fed rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4][5]18 We have previously demonstrated an important role of hyperglycemia-induced ET-1 expression in increased ECM protein deposition. 4,15,18 We have also shown that hyperhexosemia-induced increased FN mRNA expression can be prevented by bosentan treatment in retinas and kidneys of both diabetic and galactose-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Furthermore, biochemical anomalies implicated in hyperglycemia-induced vascular dysfunction such as, nonenzymatic glycation, oxidative stress, and alteration in growth factor and vasoactive factor expression are all involved in alteration of ETs and increased ECM deposition. 1,2,23,24 It is being increasingly realized that all of these hyperglycemiainduced secondary factors share the capacity to activate MAPKs. These studies suggest that MAPK activation may represent a common signal transduction of glucose-induced ET-1 mediated ECM protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Circulating ET-1 concentrations are increased in most cardiovascular diseases (CVDs), playing a critical role in the structural and functional alterations associated with the development of diabetic vascular complications and hypertension (9). ET-1 is also elevated in atherosclerotic plaques and promotes the expression of inflammatory genes in VSMCs (8).…”
mentioning
confidence: 99%